2015
DOI: 10.1053/j.gastro.2015.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic Bone Marrow–Derived Mesenchymal Stromal Cells Promote Healing of Refractory Perianal Fistulas in Patients With Crohn’s Disease

Abstract: Local administration of allogeneic MSCs was not associated with severe adverse events in patients with perianal fistulizing Crohn's disease. Injection of 3 × 10(7) MSCs appeared to promote healing of perianal fistulas. ClinicalTrials.gov ID NCT01144962.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
244
0
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 281 publications
(260 citation statements)
references
References 30 publications
6
244
0
10
Order By: Relevance
“…Crohn's disease is associated with the development of complex fistulas that are challenging to treat 141,142 . Adipose derived allo geneic stem cells have been considered as new treatment approaches for such fistulas 142,143 .…”
Section: T Cellmentioning
confidence: 99%
“…Crohn's disease is associated with the development of complex fistulas that are challenging to treat 141,142 . Adipose derived allo geneic stem cells have been considered as new treatment approaches for such fistulas 142,143 .…”
Section: T Cellmentioning
confidence: 99%
“…A summary of study characteristics is shown in Table  1, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies reported the outcome of stem cell therapy; five open label/phase I or II trials59 60, 63 65, 66, with longer‐term follow‐up61 of the cohort initially reported by Cho et al 60. in 2013.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations